Implementasi Peraturan Daerah Kabupaten Badung Nomor 7 Tahun 2012 Tentang Penataan dan Pembinaan Pasar Tradisional, Pusat Perbelanjaan dan Toko Modern (Studi Perizinan Toko Modern Jenis Minimarket CK di Kecamatan Kuta) - Wulandari, Ni Luh Yani; Yudartha, I Putu Dharmanu; Yasintha, Putu Nomy (CITIZEN CHARTER, 2018)
ABSTRACT The purpose of this study was to determine the Implementation of Badung Regency Local Regulation Number 7 of 2012 concerning Structuring and Guiding Traditional Markets, Shopping Centers and Modern Stores (CK Modern Minimarket Type Licensing Licensing Study in Kuta Subdistrict) using the Policy Implementation Policy from Van Meter and Van Horn includes policy standards and objectives, resources, communication between implementing organizations, characteristics of implementing organizations, attitudes of implementers, and social, economic and political environmental aspects. This research uses descriptive qualitative method with data collection techniques in the form of observation, interviews and documentation. The results of the study show that the implementation of Regional Regulation No. 7 of 2012 has not gone well because there are still obstacles in several indicators, namely from standard indicators and policy objectives / goals, communication between implementing organizations, attitudes of implementers, and social, economic and political environmental aspects and indicators that have been running well include two indicators, namely indicators of resources and characteristics of implementing organizations. Keywords: implementation, permit, modern store